Debunking the Myth of the Fourth Industrial Revolution - Moll, Ian (My University, 2022)
Fourth Industrial Revolution (4IR) is all the rage these days. In ideological terms, it appears to be hegemonic in its construal of our contemporary socioeconomic context, from our day-to-day interpersonal exchanges to the machinations of the global economic order. We often hear appeals to the supposed “magic” of the technology that goes with it, to resolve the economic, political and educational crises and problems of the world (and latterly, its health crises – WEF, 2020). Appeals to a 4IR usually go with a listing of a whole lot of ‘new’, ‘unprecedented’ technologies that sound smart, make us feel outdated, and leave us in awe of the future. Technologies like cyber systems, artificial intelligence, delivery drones, the internet of things, and fully autonomous killer robots.3 But it is around this misleading sense of awe – which I shall later refer to as an ideology – that my argument turns in this paper. None of these technologies necessarily warrants the claim that we are in a technological revolution, let alone a “Fourth Industrial Revolution”. I shall examine these and similar technologies, to establish my claim. The argument also runs deeper than that. An industrial revolution, properly conceived, encompasses a complex range of economic, social and cultural transformations, and there is very little evidence to suggest that we are living through a fourth one of these. A careful, deep analysis of the First, Second and Third Industrial Revolutions will make this quite clear. What we discover in these three revolutions, by way of fundamental social transformation, is not taking place in the current context of the digital, networked, information society. This paper commences with an account of the dispute between Schwab (2016) and Rifkin (2011, 2016) about whether there is such a thing as a 4IR, to provide a context for subsequent arguments. It then moves to start to develop its main argument, that there is no such thing as a Fourth Industrial Revolution. First, an account of the First Industrial Revolution (1IR) is provided, based on an examination of historical literature. This establishes analytically that this period of history was one of fundamental, transcontinental change, characterized by complex, interconnected, mutually-dependent social and socioeconomic relations and practices, as well as economic and technical innovations. The significance of the 1IR, of course, is that it is the archetypal industrial revolution in historical and theoretical terms. From this history, a framework for the analysis of any industrial revolution can be derived; this is done here to establish the criteria that any social transformation must meet if it is to count as such. Having established this analytic framework, the argument then goes on to examine the Second Industrial Revolution (2IR) and the Third Industrial Revolution (3IR). Again through an analysis of historical literature, it is established that both of these meet the criteria to be considered as industrial revolutions. They did indeed take place, to the full extent of the social, economic and cultural relations that one might expect. The 3IR is also carefully examined in relation to the aggregate of technical innovations that characterize it, because this is crucial in determining whether or not we can meaningfully claim a revolution from the 3IR to a 4IR. The resolution reached here is that there is no evidence that we are living in a contemporary, society-wide, technological revolution of any sort. The final substantive section of the paper moves on to the much more important question of whether there is a contemporary industrial revolution that is fundamentally transforming society beyond the dominant everyday, economic, social, cultural and geopolitical realities of the 3IR. It argues that it is quite clear, on the basis of all the evidence adduced, that there is no such phenomenon. The last part of the paper is more illustrative. By way of a selection of quotations from a range of sectors, it shows how the ideological frame of the 4IR as a massively converged set of global, technological marvels has spread around the world, despite the fact that it is nonsense.
Occasional Paper
The author thanks the following colleagues for generative critical comments on earlier versions of this paper: S’tha Ndlovu, Yael Shalem, Lynne Slonimsky, Barry Dwolatsky, Reuben Dlamini, David Cooper, Wayne Hugo, Yvonne Reed, Bobbie Louton, Mandla Nhlapo and James Avis.